KOHESI GRAMATIKAL REFERENSI DALAM KOLEKSI CERITA PENDEK KOMPAS - Winita, Sucia; Ramadhan, Syahrul (Jurnal Pendidikan Bahasa dan Sastra, 2019)
This study aims to find reference grammatical cohesion forms used to construct narrative discourse. This research method is a descriptive method with qualitative research. Based on the results of data analysis it was found that the reference grammatical forms of cohesion found in the March 2015 edition of Kompas Sunday's short story collection included personal, demonstrative, and comparative references. The persona reference found is person reference I consists of aku, saya, ku-, -ku, kita, and kami. The persona II reference consists of kamu, kau, -mu, and kalian. As well as reference persona III consists of ia, dia, -nya, beliau, and mereka. The demonstrative form of grammatical cohesion is found in kini, sekarang, saat ini, kala itu, dulu, siang itu, sore itu, hari itu, hari ini, di sana, di sini, ke sana, ke mana, sana, ini, and itu. As well, a comparative form of grammatical cohesion found is seperti.